A study in technology strategy: The curious case of Alfred von Tirpitz. Issue 2 (15th March 2017) - Arquilla, John
ABSTRACT: While studies of technology and war abound, the processes and reasoning that undergird choices about what to emphasize—i.e., "technology strategy"—have received much less attention. This analysis focuses upon the case of Grand Admiral Alfred von Tirpitz, who had a virtually free hand in setting German naval development strategy during the decades leading up to the outbreak of World War I. As significant technological advances characterized this period, Tirpitz's strategic choices from among a range of promising options comprise a fruitful subject of inquiry. That the current era features similarly significant technological advances and opportunities implies the possibility of drawing useful insights from the study of technology strategy in this earlier time.